2011
DOI: 10.1002/app.34251
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of copolymerization and terpolymerization of ethylene/propylene/diene monomers using metallocene catalyst

Abstract: Ind) 2 ZrCl 2 catalyst was synthesized and used for copolymerization of ethylene and propylene (EPR) and terpolymerization of ethylene propylene and 5-ethyldiene-2-norbornene (ENB). Methylaluminoxane (MAO) was used as cocatalyst. The activity of the catalyst was higher in copolymerization of ethylene and propylene (EPR) rather than in terpolymerization of ethylene, propylene and diene monomers. The effects of [Al] : [Zr] molar ratio, polymerization temperature, pressure ratio of ethylene/propylene and the ENB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…1,2 The existence of ring strain in the structure of norbornene (NBE) and its derivatives makes them facile polymerizable, thus NBE has become one of the most active participants in ethylene/cyclo-olen copolymerization. 7,[9][10][11][12][13][14][15][16][17][18][19] Catalysts play a crucial role in the production of ethylene/ ENB or ethylene/VNB copolymers, and most of catalysts reported are ansa-metallocenes. As the simplest method of functionalization, copolymerization of olen with polar monomer using early transition metal catalysts is rarely reported because of the highly oxophilic nature of polar monomer.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The existence of ring strain in the structure of norbornene (NBE) and its derivatives makes them facile polymerizable, thus NBE has become one of the most active participants in ethylene/cyclo-olen copolymerization. 7,[9][10][11][12][13][14][15][16][17][18][19] Catalysts play a crucial role in the production of ethylene/ ENB or ethylene/VNB copolymers, and most of catalysts reported are ansa-metallocenes. As the simplest method of functionalization, copolymerization of olen with polar monomer using early transition metal catalysts is rarely reported because of the highly oxophilic nature of polar monomer.…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that the degree of crystallinity (X c %) decreased as the incorporation yield augmented, that is, as the number of branches in the polymer increases, polymer crystallization becomes more and more difficult . However, there are no the fragment of [HHH] and [HHE] (or [OOO] and [OOE]) in copolymer, combined with result of rE•rH = 0 (rE•rO = 0), it is suggested that the catalysts synthesized in this article tend to be alternative copolymerization, and the 1‐hexene (or 1‐octene) comonomer is randomly distributed in the copolymer molecular chain.…”
Section: Resultsmentioning
confidence: 73%
“…Theutilization of ENB in early transition metal-catalyzed ethylene polymerization has been extensively studied. [37][38][39][40] However,t heir reactivity towards late transition metal catalysts has remained largely unexplored. In this study, ab iaryl-based phosphine sulfonate palladium catalyst (PO-Pd) was used due to its ability to generate high molecular weight polymers (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%